2020
DOI: 10.3389/fendo.2020.554941
|View full text |Cite
|
Sign up to set email alerts
|

Soy Isoflavones Accelerate Glial Cell Migration via GPER-Mediated Signal Transduction Pathway

Abstract: Soybean isoflavones, such as genistein, daidzein, and its metabolite, S-equol, are widely known as phytoestrogens. Their biological actions are thought to be exerted via the estrogen signal transduction pathway. Estrogens, such as 17β-estradiol (E2), play a crucial role in the development and functional maintenance of the central nervous system. E2 bind to the nuclear estrogen receptor (ER) and regulates morphogenesis, migration, functional maturation, and intracellular metabolism of neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 65 publications
0
20
0
1
Order By: Relevance
“…Activated PPAR γ decreased the expression levels of NF-κB [ 128 ]. The expression levels of pro-inflammatory cytokines such as iNOS, COX-2, TNF- α , IL-1 β , IL-6 were decreased in astrocytic glial cells [ 127 , 129 ], in hippocampal neurons [ 130 ], in cortical neurons [ 131 ] treated with genistein in vitro. Thus, isoflavones could protect from neuronal inflammation.…”
Section: The Role Of Isoflavones In Chronic Degenerative Diseasesmentioning
confidence: 99%
“…Activated PPAR γ decreased the expression levels of NF-κB [ 128 ]. The expression levels of pro-inflammatory cytokines such as iNOS, COX-2, TNF- α , IL-1 β , IL-6 were decreased in astrocytic glial cells [ 127 , 129 ], in hippocampal neurons [ 130 ], in cortical neurons [ 131 ] treated with genistein in vitro. Thus, isoflavones could protect from neuronal inflammation.…”
Section: The Role Of Isoflavones In Chronic Degenerative Diseasesmentioning
confidence: 99%
“…Thus, we examined the reorganization of actin filaments using cortical F-actin score (CFS) index after visualization of F-actin with Phalloidin-iFluor 594 reagent. The CFS index was determined based on F-actin cytoskeletal reorganization for each cell 43 , 44 . It was scored on a scale ranging from 0 to 3, based on the degree of cortical F-actin ring formation 0, no cortical F-actin, normal stress fibers; 1, cortical F-actin deposits extending across less than half the cell border; 2, cortical F-actin deposits exceeding half the cell border; and 3, complete cortical ring formatting or total absence of central stress fibers or both.…”
Section: Resultsmentioning
confidence: 99%
“…Primary culture of mouse cerebral cortex astrocytes was prepared as previously described 44 , 57 . Pregnant C57BL/6 strain mice were purchased from Japan SLC (Hamamatsu, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Besides, it has been reported that the in vivo administration of soybean protein hydrolysate increased the expression of brain derived neurotrophic factor (BDNF) in the cerebral cortex and the number of neurons in hippocampus and cerebral cortex, suggesting that it might promote neurogenesis [102]. Also, soy isoflavones, such as genistein, daidzein, and its metabolite, S-equol, have been informed to be an effective supplement to promote astrocyte migration in developing and/or injured adult brains, accelerating glial cell migration via GPER-mediated signal transduction pathway [103].…”
Section: Soy and The Central Nervous Systemmentioning
confidence: 99%